2019
DOI: 10.1590/1517-869220192505173969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Psychological Skill Training Program on Anxiety Levels in Top Karate Athletes

Abstract: Introduction To achieve an improvement in self-regulation, and consequently competitive performance, it is necessary to evaluate psychological skills training programs. It was hypothesized that the introduction of autogenic training and guided imagery could bring about positive changes in anxiety and self-confidence, as compared to regular training and competitive activities. Objective To investigate the effects of a psychological skills training program on the optimization of anxiety and self-confidence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…The analysis of the research data undoubtedly indicates that the implementation of psychological skills programmes makes a significant contribution to the performance of the athletes in competitions and to the development of athletes' personalities (Dehghani & Ebrahimi, 2017;Razali et al, 2017;Vesković et al, 2019). At the same time, studies also indicate that short-term intervention does not provide reliable results, however, the acquired knowledge on the benefits of psychological skills programmes and the positive experience gained in the process of acquiring various mental techniques provide athletes with additional motivation for further development of psychological skills (Kudlackova, 2011;Bryant, 2017;Mohebi et al, 2022).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…The analysis of the research data undoubtedly indicates that the implementation of psychological skills programmes makes a significant contribution to the performance of the athletes in competitions and to the development of athletes' personalities (Dehghani & Ebrahimi, 2017;Razali et al, 2017;Vesković et al, 2019). At the same time, studies also indicate that short-term intervention does not provide reliable results, however, the acquired knowledge on the benefits of psychological skills programmes and the positive experience gained in the process of acquiring various mental techniques provide athletes with additional motivation for further development of psychological skills (Kudlackova, 2011;Bryant, 2017;Mohebi et al, 2022).…”
Section: Research Results and Discussionmentioning
confidence: 99%
“…Concurring with this inference, studies have shown that the application of self-management strategy learning programs (i.e., to teach athletes how to utilize such strategies) can effectively improve the performance and psychological states of athletes in different sporting situations. For example, Vesković et al (2019) investigated the effects of two psychological strategies on anxiety and self-confidence levels in Karate athletes and found improved self-confidence and decreased cognitive anxiety among elite Karate players who underwent modified autogenic and imagery trainings compared to those who did not. O'Brien et al (2009), on the other hand, examined whether a goalsetting program could improve sports performance behaviors, competition outcomes, competitive anxiety, and self-confidence of elite and non-elite boxers; they found that, during and after the implementation of the goal-setting program, the boxers showed the following outcomes: improvements in their success rates of landed and defended punches; in their percentage of fights won; in their self-confidence; and their experienced anxieties were interpreted as facilitative rather than debilitative.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is necessary to identify appropriate strategies and intervention programs during a competitive season to contribute to reducing the levels of anxiety and stress and improving sports performance [ 15 , 16 , 17 ]. This study aimed to analyze the effects of Jacobson’s Progressive Muscle Relaxation on psychophysiological variables in male basketball athletes.…”
Section: Introductionmentioning
confidence: 99%